Alternatives to antifungal therapy for denture stomatitis: A systematic review and meta-analysis - Gowri Sivaramakrishnan; Kannan Sridharan (Wolters Kluwer Medknow Publications, 2017)
Denture stomatitis presents with inflammation of the oral mucosa beneath the denture. 90% of the cases identified Candida as a causative organism, and antifungal therapy is being commonly advocated. This systematic review and meta-analysis aim to identify disinfection of dentures as a mode of prevention of denture stomatitis to avoid the adverse effects of antifungal therapy. Literature search was performed on electronic databases. Cochrane's tool was used for assessing the risk of bias. Forest plot was generated for heterogeneity with I2 statistics and Chi-square test for the following outcome measures: Candida count, clinical improvement, recurrence of stomatitis, and adverse events. A total of five studies were found to be eligible, and the pooled estimate for Candida count was 0.39 (0.03, 0.75) was statistically significant favoring antifungal therapy. Forest plot of the relative risk of clinical cure was not significant between the groups with the pooled estimate of 1.38 (0.87, 2.18), and recurrence of stomatitis was 1.06 (0.79, 1.43). To conclude disinfectants, microwave and photodynamic therapy had similar effects on Candida in comparison to antifungal therapy. These techniques could be used as effective alternatives to antifungal therapy which aids in the prevention of adverse effects due to antifungal therapy.